The Radioecological Peculiarities of Soil Cover in Mountainous Areas (Kyrgyzstan) - Djenbaev B. М.; Dzhamanbaeva, Z. A.; Zholboldiev, B. T.; Karmisheva, U. Zh; Kaldibaev, B. K.; Zhalilova, A. A. (Advances in Social Sciences Research Journal, 2024)
The article presents the results of a radiological study of mountain soils depending on the height above sea level (740 - 760; 1600-1700 and 2000-2500 m above sea level) on the territory of the Kyrgyz Republic. Mountainous areas are characterized by denudation-erosion processes and humus; total nitrogen, gross phosphorus and potassium in the soil cover in mountainous zones are not uniform; in general, the studied zones are at the level of a natural area with small deviations, this is due to both natural and man-made processes. The content of natural radionuclides in the studied soil samples of mountain dark chestnut soils (tailing ponds and the adjacent territory) is several times higher than the average Clarke values, where a sharp decrease in the content of radionuclides is observed in the lower 20-60 cm layers, compared to mountain meadow-steppe subalpine soils. Radioecological analyzes in the city of Bishkek showed that, in general, the exposure dose is at background levels and below established standards. In the Issyk-Kul Biosphere Territory, the calculated annual doses to the population from all routes of exposure to radionuclides in the conditions of the Issyk-Kul region do not exceed the established norm (1 mSv per year). Mothballed storage facilities and dumps are a dangerous potential source of environmental pollution and therefore require constant monitoring.